Stealth Activism: Norm Formation by Japanese Courts - Frank K. Upham (Washington University Law Review, 2011)
The Article focuses on the political and social roles of the Japanese Supreme Court to the society. It argues with the remarks made by law professors John O. Haley and David S. Law about the Japanese fiduciary. It outlines the judicial decisions of court cases in various areas including employment, divorce and protection against discrimination.
Keywords: Constitutional law -- Japan; Judicial review -- Japan; Conservatism; Political questions & judicial power; Judicial process; Bureaucracy; Democracy -- Japan; Japan. Daishin' in; Jiyu Minshuto